ASUHAN KEPERAWATAN PADA BALITA YANG MENGALAMI DIARE DENGAN DEHIDRASI SEDANG DI RUMAH SAKIT UMUM dr. WAHIDIN SUDIRO HUSODO MOJOKERTO - Fikita Maulida Yulianti (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2017)
The incidence of diarrhea in Indonesian is still high as seen in the morbidity and mortality are still high. The purpose of study was to learn and practice the nursing care in infants with diarrhea with moderate dehydration through the nursing process approach included assessment, diagnosis, intervention, implementation, and evaluation. The design used in this study was a case study to explore issues of nursing care to client of under five children with diarrhea with moderate dehydration in the RSUD dr. Wahidin Sudiro Husodo Mojokerto. This case study was conducted on July 18, 2016 until July 22, 2016. From the client's assessment showed that both the client's mother said diarrhea for more than 3 times. Client looked weak, irritability, abnormal vital signs and dry mucous membranes. Nursing diagnoses that arose were fluid volume and electrolyte deficiencies related to exces secondary secretion (diarrhea). The nursing interventions were monitor signs and symptoms of dehydration, assess children's nutritional status monitor of vital signs, monitor the body weight every day, monitor laboratory examination, urge to take oral intake (ORS provision), did a collaboration of medicine administration. The action done was the provision of 200 ml ORS each time of diarrhea. Evaluation on both the client showed improved response to client’s circumstances. Based on data from the Nursing care in children with moderate dehydration diarrhea the provision of ORS of 200 ml eachtime of diarrhea is more effective if it is spent to treat dehydration. The client's family is expected to increase knowledge about the importance of maintaining the cleanliness of the food that will be consumed by clients through the local health authorities.